Adaptive Evaluation: A Complexity-based approach to Systematic Learning for Innovation and Scaling in Development - Gokhale, Siddhant; Walton, Michael (Center for International Development, Harvard University, 2023)
Nearly all challenges in international development tend to be complex because they depend on constantly evolving human behaviour, systems, and contexts, involving multiple actors, entities, and processes. As a result, both the discovery and scaling of innovations to address challenges in development often involve changes in system behaviour or even system-level transformation. This is rarely a linear process over time and can result in unexpected outcomes. Existing evaluation techniques commonly used in international development, including Randomized Control Trials (RCT) and quasi-experimental methods, are good at assessing specific effects of interventions but are not designed for the change processes inherent to innovation and scaling within a system. There is a need to reconstruct how we use existing measurement tools, techniques, and methodologies so that they capture the complexity of the environment in which an intervention or change occurs. We introduce Adaptive Evaluation, designed to learn at various levels of complexity while supporting the transformation needed to foster sustainable change. An Adaptive Evaluation uses three main approaches to work with complex questions—systems diagnosis, theorybased assessment of change processes, and iterative designs. An Adaptive Evaluation typically builds hypotheses from field-based interactions, emphasizes learning over testing, advocates open-mindedness with techniques, and appreciates the value of dialogue and participation in navigating complex processes. It can use RCT or similar techniques to analyse specific processes within a system or a development cycle, but these are embedded in a broader approach to assessment and interpretation. It is designed to be flexible and adjust to shifting contexts. Finally, an Adaptive Evaluation can be applied at any stage in a complex intervention's lifecycle, from the interpretation of the system and change processes to rapid experimentation, prototyping, and testing of select interventions, and then adaptation to different settings for impact at scale. This paper provides the theoretical basis for an Adaptive Evaluation—the main approaches, core ideology, process, and applications.

Building a culture of learning at scale: learning networks for systems change. - McKenzie, Fiona (Orange Compass & Paul Ramsay Foundation, 2021)
This scoping paper explores the question ‘what would it take to build a culture of learning at scale?’. It focuses on systems-wide learning that can help to inform systems change efforts in complex contexts. To answer this question, literature was reviewed from across diverse disciplines and the realms of education, innovation systems, systems thinking and knowledge management. This inquiry was also supported by in-depth interviews with numerous specialists from the for-purpose sector and the examination of several case studies of learning across systems. The goal was to derive common patterns to inform a ‘learning for systems change’ framework. Learning for systems change is critical when working with complexity. The dynamic nature of complex adaptive systems requires an ability to continually sense and learn from the system and adapt accordingly. This is because the nature of the challenge and ‘what works’ to meet the challenge is continually shifting (Lowe and Plimmer, 2019). This requires an ongoing process of iterative inquiry that draws upon wisdom and insights from across the system. Such learning challenges traditional siloes of expertise and organisational boundaries (Clarke et al., 2019). Learning is not simply a nice to have. It is critical for greater impact and improved outcomes, particularly in mission-driven organisations and initiatives (Price et al., 2019). In this paper, a ‘learning networks’ approach is proposed, one that draws upon individual, group and systems-wide learning to build capacity and resilience for systems change in uncertain environments. This fills a gap in the literature where the focus is largely on learning within organisations. Instead, the focus here is on what is required to support learning to occur across scales and boundaries - from the individual to system-wide. A simple meta-framework for developing learning networks is proposed that includes high level guidance on the enabling conditions - the mindsets, relationships, processes and structures- that would enable learning networks to flourish.

Monitoring, Evaluation and Learning for Systems Change - McDonald, Lizzy; Simpson, Kate; Schramm, Carolin (Wasafiri, 2025)
Today’s critical challenges are complex and require system level change. Issues like ending poverty, reversing biodiversity collapse, creating more equitable and sustainable food systems, or ending health inequalities, will not respond to neat siloed technical interventions. These are not problems we can tackle head on. Rather, we need to change the conditions (systems) that create these problems. Consequently, many of the most ambitious philanthropic foundations are adopting ‘systems change’ approaches to their work. There is a critical need to better understand the impact of systems change interventions. This is for two reasons: 1) without being able to understand our impact we can’t learn about the efficacy of efforts and focus on doing more helpful action and less unhelpful action, and 2) without effective monitoring and evaluation it is hard to galvanise resources, whether as money, time, or enthusiasm. Traditional monitoring, evaluation and learning (MEL) approaches and practices struggle to respond to complexity. Many of today’s MEL approaches have been developed to serve funders keen to ‘prove’ the efficacy of their work and hold grantees accountable. This paradigm has produced approaches like ‘logical frameworks’ that seek to create a linear logic between intervention, outputs, outcomes and impact. Such approaches often pay scant regard to the activity (intentional or otherwise) of other actors in any system, and don’t adapt well to the characteristics of complex problems such as emergence, uncertainty, and interdependency. There is a fast-developing body of practice on MEL for systems change. A growing number of practitioners are experimenting with complexity informed approaches to MEL, and UNDP is pioneering an open-source set of tools and ideas.ii Wasafiri is contributing to this innovation by developing a MEL approach that builds on our (open access) Systemcraft Framework. iii Emerging approaches for systems change MEL are underpinned by some key principles. There is growing consensus on the need to be pragmatic and flexible, not just because it is a new field for many that requires a degree of mindset and behaviour change and different ways of working. MEL approaches for system change primarily focus on improving and learning and on identifying ways to adapt and pivot. This contrasts with linear approaches to implementation and measurement. Learning questions guide and co-exist alongside indicators to support continual learning and adaptation. These shifts will require a shift in relationships between funders and implementers from measuring and accountability to greater flexibility and patience, close engagement and learning together. There is pressure to show impact in less time. Reduced time horizons, increasing impatience and integration of new sets of agendas in development programming present challenges in the context of systems change. In an increasingly resource constrained context and amid growing global uncertainty (e.g. current global politics, emergencies like COVID, economic instability, rapid technological advancement), it is unclear which direction donors will take, i.e. an even greater focus on value for money and impact, and/or willingness to explore innovative approaches and learning in uncertain territory. Wasafiri’s approach for systems MEL builds on Systemcraft. This is a diagnostic and design tool for systems change, that has been used globally across a broad range of systems and interventions. This paper summarises our approach to MEL for systems change. It aims to provide a short introductory overview and form a ‘conversation starter’ to initiate a practical dialogue on current practices, experiences, and learnings with MEL for systems change. It introduces some concepts and appropriate tools for measuring systems change and poses some key questions for further discussion. We aim to engage with funders and practitioners working on complex problems who are in the process of or planning to develop their approach to and practices for MEL, who are interested to learn, share and explore. We welcome your inputs, either in response to this document, via a call, or during online webinars that we will convene in 2025.

SystemCraft - a primer: How to Tackle our Toughest Problems - Simpson, Kate; Randall, Ian (Wasafiri, 2020)
Systemcraft is our applied framework to help leaders and organisations get started and keep going when faced with complex problems. It is built on our practical experience. It draws on a broad body of research, action and theory from the worlds of complexity thinking, systems theory, adaptive management, leadership development, social movements, development theory and beyond. Systemcraft has been designed to make systems thinking something any leader can apply when they find themselves faced with a complex problem and asking, ‘So what do I do next?’

Evaluative Inquiry for Systemic Change: A Guide to Shift Beyond Fixes to Lasting Value - Gates, Emily F.; Vidueira, Pablo (SAGE Publications, Inc, 2025)
In a world where social, ecological, health, and other problems are influenced by multiple, intersecting systems, why do most interventions target single-factor solutions? Why does so much evaluation settle for incremental change, and how could it contribute instead to deeper, lasting, transformative change? Authors Emily F. Gates and Pablo Vidueira make two interconnected arguments in this book: they critique the "fixed" approach of traditional program evaluation and policy analysis, and they advance an alternative approach centered on changing systems and developing the value of efforts toward change. They demonstrate that systemic change that embeds evaluative inquiry is a theoretically supported, practical way to work toward fundamental social change with lasting impact.

Applying Systems Thinking to Education: The RISE Systems Framework - Spivack, Marla (Research on Improving Systems of Education (RISE), 2021)
Many education systems in low- and middle-income countries are experiencing a learning crisis. Many efforts to address this crisis do not account for the system features of education, meaning that they fail to consider the ways that interactions and feedback loops produce outcomes. Thinking through the feedback relationships that produce the education system can be challenging. The RISE Education Systems Framework, which is sufficiently structured to give boundaries to the analysis but sufficiently flexible to be adapted to multiple scenarios, can be helpful. The RISE Framework identifies four key relationships in an education system: politics, compact, management, and voice and choice; and five features that can be used to describe these relationships: delegation, finance, information, support, and motivation. This Framework can be a useful approach for characterising the key actors and interactions in the education system, thinking through how these interactions produce systems outcomes, and identifying ways to intervene that can shift the system towards better outcomes.

System Innovation Network - Si Network (Si Network, 2020)
The Si Network is an online platform for building the developing of systems innovation - connecting people around the world to learn and apply the ideas and methods of systems innovation towards addressing complex challenges and building better systems that work for all. Not sure what systems innovation is? Systems innovation is a new approach to innovation that tries to tackle complex social and environmental challenges through the use of more holistic & innovation driven approaches. It is a kind of innovation that aims to change the underlying structure of a system, thus potentially enabling a more transformational kind of change - systems change - rather than incremental "innovation as usual". What Do You Do? We are building an ecosystem of individuals and organizations co-learning and co-creating systems innovation across geographies and sectors. This ecosystem is enabled by our online platform which provides educational content, toolkits, organizes events and projects as well as provides various support services for organizations. Purpose Statement Our purpose is to build the world’s capacity for systems innovation - so as to better understand and address complex challenges and co-create a world where systems work for all. We envision a world where everyone thinks in systems and has an understanding of complex systems. From this understanding, we are able to design and develop regenerative systems that work for everyone. Our mission is to grow the field of systems innovation as a pathway to co-learn the ideas of systems thinking and apply them to co-creating new systems Who's Involved? We are a networked organization of some 17K+ members forming part of 20+ hubs in major cities around the world. Our community is broad and diverse in areas of work and interest from designers, innovators, and entrepreneurs, to researchers and management but they all share a common interest in learning and applying systems thinking ideas. The Si platform is developed and managed by a small core team based in London UK. We are registered as a business but operate as a social enterprise focused on our purpose of advancing the area of systems innovation in theory and practice. Core Value Creativity - We put creativity at the centre of what we do. Holding a space for curiosity, diversity of views, exploration and critical thinking as a pathway to transformative innovation. Openness - We strongly believe in openness in our ways of being, thinking and organizing as a sustainable pathway to creating an adaptive, scalable and dynamic community. Growth Mindset - We embrace challenges as opportunities for continuous personal and collective learning and development, with a never-ending potential to grow and start with a new beginning. Perseverance - When facing uncertainty and failure, perseverance is what is needed to maintain commitment and a resilient pathway aligned with our purpose. Care - Care is one of our core principles. We foster relationships based on honesty and empathy, striving to be present and conscious in what we do and taking responsibility for the effects of our actions.